STUDI KASUS ANALISIS ASUHAN KEPERAWATAN POST PARTUM DENGAN MASALAH KEPERAWATAN NYERI AKUT DIBERIKAN TINDAKAN MASSAGE COUNTERPRESSURE - Putu Sri Eddy Farida Christiana; Ni Made Ari Sukmandari; Claudia Wuri Prihandini (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Post partum mothers experience physiological changes in uterine involution. Uterine involution in post partum mothers can cause pain in the uterus called afterpains. This raises the problem of acute pain in postpartum mothers. Management that can be done to reduce postpartum pain by providing counterpressure. Post partum mothers who counterpressure will be more free from pain, can manage fear, create feelings of comfort and relaxation. The purpose of this scientific work was carried out to determine the description of post partum nursing care with acute pain nursing problems given counterpressure massage action at Mengwi I Community Health Center. Descriptive method with a case study approach to the nursing care process carried out in managing clients with acute pain including assessment, nursing diagnosis, intervention, implementation and evaluation. Patient collection was carried out using purposive sampling technique in Mengwi I Community Health Center. The final scientific work of nurses involved three patients who were given counterpressure massage for 20 minutes. Evaluation of the action of the patient who initially experienced pain with an average scale of 6 which is classified as moderate pain and after being given counterpressure acute pain nursing problems have been resolved as evidenced by patients reporting reduced pain with an average pain scale of 3 which is included in mild pain. Giving counterpressure massage can overcome acute pain in postpartum patients so it is recommended that postpartum patients be given counterpressure massage to overcome pain.